ASSESSMENT OF PERIODONTAL STATUS AND ORAL HYGIENE STATUS CONCORDANCE LEVEL AMONG MONOZYGOTIC AND DIZYGOTIC TWINS - Bilinskyi O. Ya.; Kostenko E. Ya. (Вісник проблем біології і медицини, 2022)
Diseases of periodontal tissues, as well as caries, are a common problem among patients. The reason for the development of periodontal lesions is a complex interaction between environmental factors (level of oral hygiene, nutrition, place of living, bad habits, etc.) and genetics (hereditary predisposition). It has been established that the influence of environmental factors is covered sufficiently in scientific sources, while the role of genetic factors in the occurrence and development of periodontal diseases is insufficiently studied. One of the methods of studying the influence of the genetic factor is the use of the twin method. The aim of the work was to investigate the role of genetic factors in the formation and development of periodontal diseases by analyzing the periodontal status of monozygotic and dizygotic twins using the twin method. The research was conducted using the community periodontal index (CPI) and the Green-Vermillion hygiene index (OHI-S). After statistical processing of the results, indicators of concordance of the corresponding changes and features of the dental status among monozygotic and dizygotic twins of different sexes were established, which were presented as follows: the level of concordance of periodontal lesions among monozygotic male twins was 69.19±2.79%, among monozygotic twins female twins – 71.25±3.07%, among male dizygotic twins – 28.74±2.94%, among female dizygotic twins – 26.02±3.73%. The level of concordance of the registered index indicators of the state of oral hygiene among monozygotic male twins was 27.70±1.64%, among monozygotic female twins – 25.28±1.78%, among dizygotic male twins – 24.21± 2.27%, among female dizygotic twins – 25.09±1.56%. The obtained results can be used in the future to study the genetic component of the occurrence of caries and periodontal lesions.